2017
DOI: 10.1104/pp.16.01894
|View full text |Cite
|
Sign up to set email alerts
|

A Specialized Diacylglycerol Acyltransferase Contributes to the Extreme Medium-Chain Fatty Acid Content of Cuphea Seed Oil

Abstract: Seed oils of many Cuphea sp. contain .90% of medium-chain fatty acids, such as decanoic acid (10:0). These seed oils, which are among the most compositionally variant in the plant kingdom, arise from specialized fatty acid biosynthetic enzymes and specialized acyltransferases. These include lysophosphatidic acid acyltransferases (LPAT) and diacylglycerol acyltransferases (DGAT) that are required for successive acylation of medium-chain fatty acids in the sn-2 and sn-3 positions of seed triacylglycerols (TAGs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 52 publications
(73 reference statements)
2
38
0
Order By: Relevance
“…6 ). Similar reductions have been noted for other MCFA-producing camelina lines ( Iskandarov et al , 2017 ). The oil content of acetyl-TAG-producing lines derived from these two backgrounds was further reduced by 10–26%, depending on the specific line ( Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…6 ). Similar reductions have been noted for other MCFA-producing camelina lines ( Iskandarov et al , 2017 ). The oil content of acetyl-TAG-producing lines derived from these two backgrounds was further reduced by 10–26%, depending on the specific line ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…Previous work has shown that acetyl-TAG-producing lines in a WT background also possess slightly lower oil content ( Liu et al , 2015 a ). Interestingly, expression of a MCFA-specific DGAT1 has been shown to rescue the reduced oil content of camelina lines producing MCFAs ( Iskandarov et al , 2017 ). Here, the development of EaDAcT variants with improved specificity for MCFAs containing DAG might be helpful in overcoming the reduced oil content of these lines.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, overexpression of DGAT1 from microalgae, such as Chlorella ellipsoidea and Nannochloropsis oceanica, also led to increased oil content in Arabidopsis and B. napus (Guo et al, 2017;Zienkiewicz et al, 2017). Furthermore, DGAT1 has been used to increase the proportion of unusual fatty acids in seed oil, particularly epoxy fatty acid in G. max (coexpressed with an EPOXY-GENASE gene; Li et al, 2010a) and capric acid in C. sativa (in combination with fatty acyl-ACP thioesterase B1 and LPAAT from Cuphea viscosissima; Iskandarov et al, 2017). Similar to DGAT1, seed-specific overexpression of fungal DGAT2 resulted in enhanced seed oil content in G. max (Lardizabal et al, 2008) and Z. mays (Oakes et al, 2011).…”
Section: Biotechnological Applications Of Plant Dgat and Pdatmentioning
confidence: 99%
“…acyl‐ACP thioesterases, phospholipid:diacylglycerol acyltransferases, diacylglycerol acyltransferases, lysophosphatidic acid acyltransferases) with high activity towards the unusual fatty acid. The low or modest amounts of unusual fatty acids produced in transgenic seeds expressing genes for production of the particular fatty acid have been significantly enhanced by co‐expressing genes encoding some of these auxiliary enzymes (Burgal et al ., ; Kim et al ., ; Iskandarov et al ., ). Thus, seeds with high amounts of unusual fatty acids have recruited, or developed, a number of highly specialized enzymes to ensure that the produced fatty acid is efficiently channeled into the oil and excluded from membranes.…”
Section: Resultsmentioning
confidence: 97%